STRATEGI PENDIDIKAN LITERASI DIGITAL YANG KREATIF DAN MENYENANGKAN DI PEDESAAN - Aisyah, Risa; Sawaludin, Yunus; Vergania, Ripani; Mashfufah, Shofiyyatul; Fauzi, Irvan Rizki; Nasir, Muhammad; Azahra, Sarah; Alim, Ali Ahmad Nur; Raysona, Mochamad Fikar; Sari, Savina Tika; Nirwana, Luki Ahmad; Nurhalizah, Alya Adha; Fauzyah, Salma; Nugraha, Rifky Surya; Doank, Herdi; Khadafi, Muhammad Habil; Nuriman, Nuriman; Agnia, Pahrul Rizal Yasvin; Solehudin, Bayu; Fachrezi, Muhamad Daffa (Jurnal PkM MIFTEK, 2023)
This research discusses the implementation of creative and fun digital literacy education strategies in Sukasenang village. The goal is to increase students' understanding of digital literacy, develop skills needed in a technological society, and create a fun learning experience. The learning method used is the jigsaw model, where students work in small groups with various abilities. This program uses written and audio visual media to support students' understanding. The method used is a qualitative descriptive approach with 4 types of activity stages that have been implemented, consisting of: program socialization stage, training stage, implementation stage and evaluation stage. The evaluation results show that the learning method applied by KKN group 17 is appreciated by students, with 85% of students liking it. However, there are still challenges in increasing students' interest in the learning process. This program has the potential to have a positive impact on the development of digital literacy in rural areas and innovative learning methods. It is hoped that the continuation of this program will help students be more active in learning digital literacy and encourage innovation in education. This research shows that implementing creative and fun digital literacy education strategies can be an effective alternative in increasing digital literacy in rural environments.